Development on polymeric precursor routes to produce superconducting nanoparticles - Lisboa Filho, Paulo Noronha [UNESP]; Motta, M.; Saeki, Margarida Juri [UNESP] (Elsevier B.V., 2007)
The well-known polymeric precursor route is a simple and low-cost sol-gel method based on the preparation of an aqueous precursor solution of metals followed by the addition of a water-soluble polymer. This method consists of a polyesterification process between a metal chelate complex by using a hydroxycarboxylic acid and a polyhydroxy alcohol. In this work, citric acid (CA), tartaric acid (TA) and ethylenediaminetetraacetic acid (EDTA) are used as the hydroxycarboxylic acid and ethylene glycol (EG) is used as the polyhydroxy alcohol. The effects of the precursor pH solution, time and temperature of polymerization step as well as the combination of different chelating agents in order to obtain nanoscopic YBa2Cu3Oy samples were traced. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: superconducting materials; chemical synthesis; size effects